2020
DOI: 10.1177/1096348020967068
|View full text |Cite
|
Sign up to set email alerts
|

The Reciprocal Role of Trust in Customer Value Co-Creation

Abstract: The main purpose of this research was to investigate the reciprocal nature of trust in a service provider, established through consumer involvement in value co-creation. Grounded in service-dominant logic and social exchange theory, the study used an existing consumer-generated co-creation contest by a popular U.S.-based coffee-shop brand. When examining customer involvement with value co-creation (N = 510), the covariance-based structural equation model test of recursive versus sequential trust models reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 71 publications
0
21
0
4
Order By: Relevance
“…This approach led to two additional publications (i.e. Shulga et al, 2021 andZadeh et al, 2019), examining the inclusion, exclusion and quality criteria by analyzing titles, abstracts and full texts. Finally, 59 research articles were included as a definitive source for the review study.…”
Section: Stage 2: Identify and Evaluate Articlesmentioning
confidence: 99%
See 2 more Smart Citations
“…This approach led to two additional publications (i.e. Shulga et al, 2021 andZadeh et al, 2019), examining the inclusion, exclusion and quality criteria by analyzing titles, abstracts and full texts. Finally, 59 research articles were included as a definitive source for the review study.…”
Section: Stage 2: Identify and Evaluate Articlesmentioning
confidence: 99%
“…Moreover, consumers who dedicate resources to CBC on social media are likely to engage with the brand (Harrigan et al, 2021), which increases the strength of the relationship between consumers and the brand. As a result, various constructs related to brand relationship strength are widely employed as consequences of CBC in the social media context, for example, customer brand engagement Harrigan et al, 2021); brand involvement (Shulga et al, 2021;Sanz-Blas et al, 2019); brand attachment (Sanz-Blas et al, 2019); and brand trust (Acikgoz and Tasci, 2021).…”
Section: Customer Brand Co-creation On Social Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…Trust is defined as customer expectations that service providers are dependable and reliable in fulfilling their promises (Sirdeshmukh, Singh, & Sabol, 2002). Customer trust can be built and maintained through cocreation with customers (Busser & Shulga, 2018;Iglesias, Markovic, Bagherzadeh, & Singh, 2018;Shulga, Busser, Bai, Kim, & Research, 2021). Massey and Kyriazis (2007) stated that customer engagement in intensive communication during a new product co-development increases customer trust in the company.…”
Section: Degree Of Co-creation and Customer Trustmentioning
confidence: 99%
“…The theory used in this study is Social Exchange Theory which propounds that people weigh their cost of any social decision they make in comparison to the reward or benefit they receive from that social interaction (Shulga et al, 2021). Multiple previous studies have demonstrated the concept of customer loyalty underpinning Social Exchange Theory (Shulga et al, 2021) and illustrate that Both costs as well as benefits are found in tangible or intangible forms (Ferm & Thaichon,202). Money and time are tangible forms (Hou & Zhang, 2021) whereas emotions, efforts and behavioral aspects like price, respect and power are intangible forms (Lakan & Yani, 2021).…”
Section: Underpinning Theorymentioning
confidence: 99%